Literasi Media Sebagai Bentuk Etika Komunikasi Islam - Suci Ramadhani; Irma Yusriani Simamora (Prodi Perpustakaan dan Sains Informasi, 2022)
In communicating, of course, good communication skills and skills are needed which can create mutual understanding in communication. Communication messages will be conveyed properly if the delivery of messages is carried out with good communication ethics. Media is an effective means of communication used in the era of communication technology. This research uses descriptive qualitative research methods with data collection methods through literacy studies and then analysis is carried out with field conditions so that it can be concluded that good literacy skills in sorting and selecting media content are a form of communication ethics which are also related to Islamic communication ethics.